PEMBERITAAN BUY-BACK INDOSAT (Study Analis Framing Model Gamson dan Modigliani Pada Pemberitaan Media OnlineViva.co.id dan DetikNews.com) - Laili Zulfa (AL-IDZA'AH: Jurnal Dakwah dan Komunikasi, 2021)
Campaign activities are one of the strategic that are often used by presidential candidate to win the election. In campaign activities, presidential candidate try to gain popularity and electability the voters. Usually to realize this, the success teams occupied themselves with the casuistic questions that were in each candidate pair. So the role of the media is very important. In this case the function of the media is nothing but to overthrow political opponents in addition to seeing their political friends. This article as a whole discusses how the media focus on reporting on some of the upcoming casuistic candidates, namely backing Indosat. The author will use online media detiknews.com and viva.co.id, which are the ideologies of the two media, both of which support the number one candidate pair. but the news produced from the two media is slightly different. Through the analysis of framing William A. Gamson and Modigliani the author will look at how the differences in packaging of the two media are in constructing Indosat buy-back news.